Rancang Bangun Aplikasi Inventori Berbasis Web Di Bengkel Babeh Kaujon - Muhammad Hernandi; Fajar Septian (CV. Multi Kreasi Media, 2023)
The inventory system is a system designed for goods data management purposes, one example of this system being implemented at Babeh Kaujon Workshop, which is located at Jl. K.H. term. Ma'mun Blok Haji Ali No.35, RT.3/RW.2, Serang, Kec. Serang, Serang City, Banten 42116. At this time the management of goods in the workshop is still using a simple system resulting in a lot of goods going out without a record of goods coming out so that the workshop owner wants to simplify the management of goods data with computerization which hopes to increase the effectiveness of work in managing goods. So with that, a web-based inventory system application is designed so that it is easier for owners to manage incoming and outgoing goods using the PHP language and MySQL database. In addition, using this system hopes to improve the quality of service in searching for goods and the possibility of the risk of data loss will be reduced because it is stored safely and neatly in the database.